LEGAL PROTECTION OF CHILDREN AS VICTIMS OF SEXUAL CRIMES COMMITTED BY PERSONS WITH DISABILITIES - Rinani, Earlyn (Jurnal Kajian Ilmu Hukum, 2024)
Children as the younger generation are the greatest wealth for the family, society and nation. They are components that have a big responsibility in determining whether the country will experience progress or decline. Article 28 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia states that "Every child has the right to survival, growth and development and the right to protection from violence and discrimination". Sexual violence is a form of violence that can occur both in public and at home. Individuals who are often victims of sexual violence cases are usually women and children, who are often considered to be in a weaker position. Perpetrators of sexual crimes often target children as victims because they feel that children will not understand that these actions are against the law, or because they think children will not dare to resist.The research used in this scientific paper is a type of normative juridical research, a legal research method that involves secondary data analysis or literature study. Persons with disabilities who are involved in sexual crimes can be accused if there is sufficient evidence to support the crime. This means that the perpetrator's status will change from suspect to defendant when sufficient evidence is met. The reasons for child protection are very reasonable because children are individuals who have not yet reached physical and mental maturity.